2015
DOI: 10.1016/j.cognition.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an eye on serial order: Ocular movements bind space and time

Abstract: The present study examined whether traveling through serially-ordered verbal memories exploits overt visuospatial attentional resources. In a three-phase behavioral study, five single-digits were presented sequentially at one spatial location in phase 1, while recognition and verbal recall were tested in phases 2 and 3, respectively. Participants' spontaneous eye movements were registered along with the verbal responses. Results showed that the search and the retrieval of serially-ordered information were medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 64 publications
2
49
1
Order By: Relevance
“…Serial order turned out to be nonsignificant in both analyses (F < 1) and had no impact on the other results. While the absence of an effect of serial order on eye movements during recognition is in line with previous studies (Rinaldi et al, 2015), the absence of such an effect during memory recall is new.…”
Section: Prediction Of Eye Gaze Position During Retrieval Processes Bsupporting
confidence: 89%
See 1 more Smart Citation
“…Serial order turned out to be nonsignificant in both analyses (F < 1) and had no impact on the other results. While the absence of an effect of serial order on eye movements during recognition is in line with previous studies (Rinaldi et al, 2015), the absence of such an effect during memory recall is new.…”
Section: Prediction Of Eye Gaze Position During Retrieval Processes Bsupporting
confidence: 89%
“…The degrees of freedom were obtained by a Satterthwaite approximation (Fai & Cornelius, 1996) Recent studies have shown serial order effects in the mental number line (e.g., van Dijck & Fias, 2011), that is, an association between the left side of space and early items on a remembered sequence, and between the right side and late items of a sequence. Rinaldi, Brugger, Bockisch, Bertolini, and Girelli (2015) even found such an effect on eye position during memory recall. In order to further explore the role of serial position on eye movements, we repeated the analysis for memory encoding and free recall with the additional predictor serial order (position of the item during encoding).…”
Section: Prediction Of Eye Gaze Position During Retrieval Processes Bmentioning
confidence: 90%
“…The second "ocular time line" finding relates to serial recall: our eyes look along a left-to-right mental time line during recall tasks. When recalling (by speaking them out) serial items (five random digits), then the eyes look furthest to the left for the item that has been presented/encoded first-and the more recently the items have been presented/encoded, the more the eyes look to the right (Rinaldi, Brugger, Bockisch, Bertolini, & Girelli, 2015). The third "ocular time line" finding relates to online auditory processing of temporal-relation words like before-that (German: vorher) and after-that (German: nachher).…”
Section: Embodied Domainmentioning
confidence: 99%
“…Using the just discussed empirical findings (Hartmann et al, 2014;Rinaldi et al, 2015;Stocker et al, in revision) as a basis, I propose that the temporal-episodic information in relation to (2) is projected along a time line in peripersonal space in front of our body. As episodic processing suggests a left/down-to-up/right time line (Hartmann et al, 2014), I will provisionally assume that such a time line is involved when a speaker is processing a memory by uttering a statement like (2).…”
Section: Embodied Domainmentioning
confidence: 99%
“…Rinaldi, Brugger, Bockisch, Bertolini, & Girelli, 2015). After partialing out the number of cards, the total hand value remained a significant predictor of both x-coordinates (M = 0.022°/value, SD = 0.030, 95 % CI: 0.011, 0.033), t(29) = 4.11, p = .0003, d = 0.75, and y-coordinates (M = -0.032°/ value, SD = 0.042, 95 % CI: -0.048, -0.017), t(29) = 4.19, p = .0002, d = 0.76.…”
Section: Resultsmentioning
confidence: 99%